The Influences of Rootstock on the Performance of Pinot Noir (Vitis vinifera L.): Phenological Progress, Physiological Performance, and Petiole Nutrient Status - Yipeng Chen; Yanan Fei; Alexis Pang; Mark Krstic; Peter Clingeleffer; Kate Howell; Deli Chen; Pangzhen Zhang (Australian Journal of Grape and Wine Research)
Background and Aims. Rootstocks are widely utilised in viticulture industry to prevent the infestation of phylloxera, but they may affect the growth and performance of the scion. This project investigated the impacts of 14 different rootstocks on the phenological, physiological, and nutritional performance of the scion using Vitis vinifera L. cv. Pinot noir MV6. Methods and Results. Two commercial vineyards located in the Mornington Peninsula wine region of Victoria, Australia, reflect two types of mesoclimate. At both vineyards, the scions of V. vinifera L. cv. Pinot noir clone MV6 were grafted onto 14 rootstocks including 101-14 Millardet et de Grasset (101-14 Mgt), 1103 Paulsen, SO4, 110 Richter, Schwarzmann, 5C Teleki, 3309C, Merbein 5489, Merbein 6262, Merbein 5512, C20, C29, C113, and C114, with own roots acting as a control group. Anthesis time, veraison time, pruning mass, external leaf area index (LAI), plant hormone, and petiole nutrients were measured over three growing seasons from 2018 to 2021. Most rootstocks showed earlier anthesis compared to own roots at both vineyards. Rootstocks 110 Richter and Merbein 5512 had a 40% reduction in the leaf area index and more than 60% reduction in pruning mass compared to the control group at the Robinson Vineyard. Notably, the pruning mass of grafted vines was positively correlated with the concentration of indole-3-acetic acid in roots and salicylic acid in leaves in the present study. Rootstocks demonstrated a clear influence on the nutrient status of the grafted vines. All rootstocks, especially 3309C, C113, and C114, inhibited the accumulation of phosphorus in petioles compared to ungrafted vines. Rootstocks 3309C and C20 increased the potassium content in the petioles of grafted scions by 15% and 31%, respectively, while Merbein 5489 and Merbein 5512 reduced potassium content in petiole by 54% and 48%, respectively, compared to ungrafted vines at both vineyards during the three growing seasons. Conclusions. Grafting Pinot noir onto the observed rootstocks in this study affected the phenological progress, physiological performance, and petiole nutrient status. Rootstocks 101-14 Mgt and Schwarzmann showed a similar progress of anthesis to own-rooted Pinot noir, slightly earlier progress of veraison, limited impact on canopy density and pruning mass, and no deficiency of nutrients in the petiole. Thus, these two rootstocks are considered vigorous options for Pinot noir MV6 in cool climates. The performance of Pinot noir grafted to C-series rootstocks (C20, C29, C113, and C114) needs further evaluation due to their younger age in both vineyards. Significance of the Study. The present study provided results reflecting the impacts of grapevine rootstocks on Pinot noir scion performance, which support rootstock selection for Pinot noir. The results of this study provided guidance to vignerons in selecting suitable rootstock to manage grapevine’s phenological development, vegetative growth, and nutrient status in cool clime regions.